ANALYSIS OF CITY POLICY IMPLEMENTATION WITHOUT THE SLUM MINISTRY OF PUBLIC WORK AND HOUSING IN LANGSA - Ade Miranda (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2019)
ABSTRACT, The population settlements of Langsa city which has been increasingly crowded since the last 3 years, has been designated as one of Langsa's slums in Aceh province. In Presidential Decree No. 2 of 2015 on Medium Term Development plan (RPJM) 2015-2019 mandated the development and development of urban areas through the handling of slum quality and prevention of growing the region New slums and sustainable livelihoods. The purpose of this research is to analyze the implementation of the urban without slum policy (KOTAKU) Ministry of Public Works and people's housing in Langsa City and to know the role of the Government in the settlement of slums in Langsa city. The method in this study is a qualitative disclaimer with data analysis techniques using the policy implementation theory of Jeffrey Pressman and Aaron Wildavsky, covering the classification of planning, analysis, designing, implementation, and maintenance. The results of this research are first, the implementation of KOTAKU's policy has been implemented from 2016 until now but not completely evenly in the area of Langsa city, and still found a stage of analysis that has not been fully executed. Secondly, the Langsa municipal government plays an active role by formulating the KOTAKU program in RPJM 2017-2022, and Human Resources (HR) Constraints are found in shaping the group of NGOs (KSM) as a group that runs the form of implementation KOTAKU's program in the village. The conclusion of this research is Langsa city government as well as related parties have not fully succeeded in handling slum in Langsa city. The government must conduct a mature formulation based on slum data that is in data correctly to obtain the value of its severity and to establish slum and to do HUMAN development by providing training to Knowledge of work procedures.Keywords: Policy implementation, City without slum, Public works office and People's housing Langsa city